Oxidation of indolic bases by cytochrome P450 and ferrous picolinate. Issue 2 (1997) - Jankowski Jankowski, K. K.; Delaforge Delaforge, M. M.; Jaouen Jaouen, M. M.; Virelizier Virelizier, H. H.
Abstract : Oxidations performed on four indolic bases, β ‒carboline1, ibogaine2, reserpine3 and ajmaline4, by hepatic cytochrome P450 (Cyt. P450) and ferrous picolinate (Fe(PA)2 ), lead to alicyclic hydroxylation as major reaction products.